Fatty acid composition in a cultured marine harpacticoid, Amphiascoides neglectus - Kassim, Zaleha; Mat Nasir, Nasiratul Shahida; Hasnan, Hazwani Hanim; Jauhad, Kamaruddin (Knowledge Transfer Programme © Knowledge Transfer Centre, 2017)
Lipid content especially fatty acids are used by animals for their growth, reproduction and neural development particularly in zooplankton and fish. Thus, it is important to produce live feed copepods with reasonable fatty acids content for aquaculture use. This information and technique is planned to be transferred to the industrial partner, Flexible Tech Sdn. Bhd. In this study, salinity has been used as independent variable to culture harpacticoid copepod (Amphiascoides neglectus) in the open hatchery under ambient temperature for four months. The culture was done with 5 replicates in 250ml glass container at 30ppt and 20ppt. At the end of the experiment, fatty acid compositions of harpacticoid copepods were determined using GC-MS for both salinities. From the result, harpacticoid copepods cultured under salinity 30ppt showed more fatty acids variety than salinity 20ppt. It is shown also to have higher total fatty acid number compared to salinity 20ppt (30 and 15 fatty acids respectively). The existence of EPA (eicosapentaenoic acid) which is an essential fatty acid (EFA) was detected in salinity 30ppt even though with very low concentration (0.01±0.02). Salinity 30ppt is a favorable salinity treatment to be used in copepods culture in order to get EPA existence while considering other parameters such as temperature, pH and diet used. Graduate Interns (GI) were trained to impart the technique to culture high fatty acid copepods by maintaining the salinity at 30ppt.This information was then use for marketing purpose of the product.